Laser-Induced Reactions of 4-Aminobenzenthiol Species Adsorbed on Ag, Au, and Cu Plasmonic Structures Followed by SERS Spectroscopy. The Role of Substrate and Excitation Energy - Surface-Complex Photochemistry and Plasmonic Catalysis - Kopal, Ivan; Švecová, Marie; Jeřábek, Vojtěch; Palounek, David; Čapková, Tereza; Michalcová, Alena; Lapčák, Ladislav; Matějka, Pavel; Dendisová, Marcela (ACS omega, 2024)
This study focuses on investigating the laser-induced reactions of various surface complexes of 4-aminobenzenethiol on Ag, Au, and Cu surfaces. By utilizing different excitation wavelengths, the distinct behavior of the molecule species on the plasmonic substrates was observed. Density functional theory (DFT) calculations were employed to establish the significant role of chemical enhancement mechanisms in determining the observed behavior. The interaction between 4-aminobenzenethiol (4-ABT) molecules and plasmonic surfaces led to the formation of surface complexes with absorption bands red-shifted into the visible and near-infrared regions. Photochemical transformations were induced by excitation wavelengths from these regions, with the nature of the transformations varying based on the excitation wavelength and the plasmonic metal. Resonance with the electronic absorption transitions of these complexes amplifies surface-enhanced Raman scattering (SERS), enabling the detailed examination of ongoing processes. A kinetic study on the Ag surface revealed processes governed by both first- and second-order kinetics, attributed to the dimerization process and transformation processes of individual molecules interacting with photons or plasmons. The behavior of the molecules was found to be primarily determined by the position and variability of the band between 1170 and 1190 cm-1, with the former corresponding to molecules in the monomer state and the latter to dimerized molecules. Notably, laser-induced dimerization occurred most rapidly on the Cu surface, followed by Ag, and least on Au. These findings highlight the influence of plasmonic surfaces on molecular behavior and provide insights into the potential applications of laser-induced reactions for surface analysis and manipulation.